THE TRACES OF ORIENTALISM IN THE ATTEMPS OF MODERNISATION IN ISLAM - Keskin, Ibrahim (Ilahiyat Bilimleri Arastirma Vakfi, 2012)
Orientalism refers to how the West understands and interprets the eastern societies. Such understanding and interpretation goes hand in hand with the imperialist expansion and subserves to strengthen and justify the position of the West. The decline of the Islamic world caused internalization of the orientalist discourse by the intellectuals of the Islamic world. When focused on the evaluations of these intellectuals regarding the periodization and classification of the historical processes and their approach to the problem of backwardness, it is possible to see the traces of Orientalist viewpoint.
Keywords: Orientalism; Islam; Modernisation; West; East; Imperialism; Self-Orientalism